Sport Policy in Canada - Lucie Thibault, Jean Harvey (University of Ottawa Press, 2013)
The purpose of this book is to provide a comprehensive overview of current Canadian sport policy. More than ever, in order to understand the role and meaning of sport in society, it is important to recognize the inter-relations between the sport system and the state, to realize that numerous sport issues are indeed also public policy issues in which the state has a key role to play. Given the current international trend toward devoting increasingly large sums of money to ‘produce’ Olympic medalists, to what extent should governments support high performance athletes, and through which channels? To what extent should municipalities provide access to sport infrastructures, free of charge or through user fees, to their citizens and community clubs? Should the federal government financially support national sport organizations (NSOs)? At what level? Under which conditions? Should governments establish public administrative bodies to control doping in sport, or should they mandate non-governmental organizations to do so? These are only a few examples of issues that first come to mind when one considers the role government plays in sport. There have been prominent developments in sport in recent decades that reinforce government’s central role in the field. Canadians remember the success of Canadian athletes at the Vancouver 2010 Olympic and Paralympic Winter Games, as well as the massive investments of the federal government, the province of British Columbia and the city of Vancouver which made the hosting of these games successful. Canadian sport leaders, with funding from the government and sponsorships from the private commercial sector, launched the creation of Own the Podium, an initiative that continues to establish specific performance targets and strategies to achieve these targets for upcoming Summer and Winter Olympic and Paralympic Games.